Das Bedingungslose Grundeinkommen - ein tragfähiges Konzept? - Thomas Straubhaar; Götz W. Werner; Wolfgang Eichhorn; Lothar Friedrich; Florian Habermacher; Gebhard Kirchgässner; Heiner Flassbeck; Georg Quaas; Sebastian Thieme (Wirtschaftsdienst, 2013)
In der Schweiz betreibt eine Initiative aktuell ganz konkret einen Volksentscheid mit dem Ziel, ein bedingungsloses Grundeinkommen einzuführen. In Deutschland wird das Konzept lebhaft diskutiert. Allerdings wird seine Wirkung auf Beschäftigung, Besteuerung, Einkommensverteilung und die Bereitstellung von staatlichen Leistungen ganz unterschiedlich beurteilt. – – The introduction of an unconditional basic income has been discussed in Switzerland for many years. Germany, however, takes a sceptical view of this idea. The authors of this 'Zeitgespräch' express disparate opinions on how broadly the concept should be defined, but they agree on the motive behind the concept: respect for human dignity. Moreover, it may make many social policy rules obsolete. There are conflicting opinions concerning the reaction of labour supply to the unconditional basic income. Some authors fear that it will shrink substantially. But its financing will be the main problem. There are proposals to increase the value added tax rate. The economic impacts of funding it by income tax revenues are analysed using a macroeconomic model. Ultimately, the implementation of the concept will have distributional effects which are very difficult to predict.
Keywords: H53; I38; J24; 330; Grundeinkommen; Wirkungsanalyse; Deutschland